Divertor closure effects on the TCV boundary plasma. (June 2021) - Février, O.; Reimerdes, H.; Theiler, C.; Brida, D.; Colandrea, C.; De Oliveira, H.; Duval, B.P.; Galassi, D.; Gorno, S.; Henderson, S.; Komm, M.; Labit, B.; et al.
Abstract: The Tokamak à Configuration Variable (TCV) has recently been equipped with gas baffles to increase its divertor closure for a broad range of divertor magnetic geometries. First experimental results reported in Reimerdes et al. (2021) demonstrated compatibility with a broad range of divertor magnetic geometries and confirmed the main design constraints of the baffles, in particular an increased divertor neutral pressure. The present article presents a more in-depths analysis and extended experiments of this first baffle assessment on the TCV boundary plasma. It is shown that the divertor neutral pressure increased following the installation of the baffles, as predicted by SOLPS-ITER and SolEdge2D-EIRENE simulations. Varying the divertor closure by changing the position of the plasma showed that the plasma equilibrium designed to assess the baffle effect was not far from the optimal trade-off between plasma plugging and recycling on the baffles. The baffles facilitate access to a partially detached regime in both L- and H-modes. In L-Mode, with the ion ∇ B -drift directed from the X-Point to the plasma core, a reduction of the line-averaged density detachment threshold by approximately 20% is observed at the outer target, while inner strike point detachment is only achieved in the presence of baffles. Multispectral imaging shows that the CIII front moves from the outer target towards the X-Point at a lower line-averaged plasma density, indicating a colder outer leg. In H-mode, the CIII front is generally located near the X-Point between the ELMs, while without baffles, N 2 -seeding is required to move the front up to that location. Highlights: TCV has recently been equipped with gas baffles to increase its divertor closure. The baffles increase the divertor neutral pressure by a factor 2-5 in Ohmic discharges. The baffles reduce the core density needed for detachment by ∼ 20% in Ohmic discharges. The baffles facilitate access to colder divertor plasmas in H-mode.